Clitic positioning in Croatian and functional sentence perspective - Peti-Stantić, Anita (Array, 2009)
I understand the scrambling as semantically driven notion which affects syntactic, semantic and information-structural properties of a sentence. Although all western South Slavic languages are canonical scrambling languages, clitics and clitic clusters present a special problem because they tend to be much more restricted in their distribution than the other word classes. For that reason I will present the types of Croatian clitic placements that have been the source of much controversy in contemporary linguistics and try to explain them. As noted, language such as Croatian, although claimed to be robust Wackernagel type languages, permit many unexpected clitic/clitic cluster positions. These positions involve the following phenomena: 1. Clitic positioning lower than second position (“clitic third” or “delayed clitic placement”) 2. Clitic positioning apparently internal to or “splitting” NPs. The actual type of phenomena can be illustrated by the following sentences: (1) a. Od jučer ga prodaje za velike novce. (no splitting ; neutral reading) ‘Since yesterday (s)he’s selling it for big bucks.’ b. Od jučer prodaje ga za velike novce. (no splitting ; neutral reading) ‘Since yesterday (s)he’s selling it for big bucks.’ c. Za velike ga novce prodaje od jučer. (neutral reading preferred) ‘Since yesterday (s)he’s selling it for big bucks.’ d. Od jučer prodaje za velike ga novce. ‘Since yesterday (s)he’s selling it for big BUCKS.’ or ‘Since yestedrday (s)he’s selling it for BIG bucks.’ or JUST ‘Since yesterday (s)he’s selling it for big bucks.) e. *Od jučer prodaje za ga velike novce. (Bold = clitic, underline = constituent being split) Since these sentences differ radically from what has been reported in the literature, I hope to be able to show that they can be consistently explained by an overarching functional perspective that polices both syntax and phonology to determine which scrambling possibilities are acceptable.